Realization of PIC-Controlled hardware and Simulink model of frequency regulation using HHO algorithm - Ulaganathan, Meenakshi Sundaram; Muniraj, Rathinam; Suresh, Vaikundam; Raja, Sundararajan Edwin; Jarin, Thankaswamy (AIP conference proceedings, 2024)
In this paper is used to maintain the turbine frequency in the desired range. Here the requirements of the load and generation is monitored constantly. In this hardware and software models are proposed to control the reactive power and real power for the control of frequency continuously. In the proposed scheme, a hardware model consisting of varying real power and reactive power is realized for continuous frequency control. In today’s power plants, the valves are generally opened and closed when the frequency exceeds the tolerance limit. This creates a high stress on the turbine fluid. The regulating valve eliminates the stress of the turbine by closing the valve and opening the valve. Here the Proportional and Integral (PI) based Harris Hawks Optimization (HHO) is used to eliminate the frequency deviation. through the Proportional and Integral (PI) based Harris Hawks Optimization (HHO).